(untitled) (University of Khartoum Engineering Journal, 2022)
The main objective of this paper is to determine object coordinates of points using digital aerial images by employing co linearity condition equations. The iterative solution was used to solve the co linearity condition equations to determine the exterior orientation parameters of a stereo pair. This was followed by determining the three-dimensional ground space coordinates of check points using photogrammetric measurements. Bahry industrial area was used as a test image. Image coordinates were measured by scanner. The ground coordinates of the same points were determined using real time kinematic GPS. The results were compared with their corresponding computed values using analytical photogrammetric measurements. The three-dimensional ground coordinates of points were used to generate a contour map from a real time GPS and Photogrammetric data. The obtained Root Mean Square error (RMSE) in X, Y, Z coordinates were found to be ±0.562 m, ±0.488 m, and ± 0.629 m, respectively.